1978
DOI: 10.1093/bja/50.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Misplacement of Nasogastric Tubes and Oesophageal Monitoring Devices

Abstract: Accidental invasion of the trachea past an inflated cuff may occur more easily when endotracheal tubes with soft, low pressure cuffs are used. A new, simple and safe technique for blind oesophageal intubation is outlined. Two cases of accidental invasion of the trachea by oesophageal tubes are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The routine way for NGT insertion is its blind insertion while the patients head is in the neutral position with an approximate success rate of 40-58% [17][18][19]. Although common techniques for NGT insertion are lateral neck pressure, head flexion, freezing the NGT before its insertion, anterior larynx displacement, slit ETT as introducer, as well as lateral head positioning, none of them has reported high success rate [17][18][19][20][21] (Table 1). For the first time, Siegel et al showed that a nasopharyngeally placed endotracheal tube could facilitate the insertion of a difficult nasogastric tube [55].…”
Section: Insertion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine way for NGT insertion is its blind insertion while the patients head is in the neutral position with an approximate success rate of 40-58% [17][18][19]. Although common techniques for NGT insertion are lateral neck pressure, head flexion, freezing the NGT before its insertion, anterior larynx displacement, slit ETT as introducer, as well as lateral head positioning, none of them has reported high success rate [17][18][19][20][21] (Table 1). For the first time, Siegel et al showed that a nasopharyngeally placed endotracheal tube could facilitate the insertion of a difficult nasogastric tube [55].…”
Section: Insertion Techniquesmentioning
confidence: 99%
“…Using macintosh laryngoscope or glidescope with assistance of magill forceps [26,27] Ultrasonography Nose bleed Infectious complications [10] Neck flexion Uretral guidewire [25] Nex method [14,15] Sinusitis [46] And intracranial placementand central nervous system complications [48] Lateral head positioning I-gel [28,29] Under water vaccum effect [35] Parotitis [46] Nose erosion/ /nasal aral necrosis [49] Anterior displacement of the mandible (and a group of older techniques) [21] Proseal LMA [28,29] Aspirate colors [35] Sore throat Laryngeal edema with asphyxia…”
Section: By Equipment Minor Majormentioning
confidence: 99%
“…The Steen technique, which, with some modifications, involves passing the NG tube through an endotracheal tube already inserted into the esophagus, is favored by some authors (4, 5). The finger-guided method (6) and puffing technique (7) have also been reported to be successful. However, because these are all blind techniques, these measures can be traumatic and unreliable.…”
Section: Casementioning
confidence: 99%
“…Because of the reshaping force culties in inserting NG tubes, not always in comatose or anesthetized patients (l), but also in conscious patients in whom normal anatomy above the cricopharyngeous muscle is distorted. A variety of measures that facilitate insertion have been mentioned in the literature (1)(2)(3)(4)(5)(6)(7). To overcome the flexibility of NG tubes, not only chilling the tube, but also Fogarty catheters (I), guitar strings (4, and stainless steel spring guides (3) have been advocated as stylets to increase the tube's stiffness.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation